Dietary nitrate supplementation improves sprint and high-intensity intermittent running performance - Thompson, Christopher; Vanhatalo, Anni; Jell, Harry; Fulford, Jonathan; Carter, James; Nyman, Lara; Bailey, Stephen J.; Jones, Andrew M. (Nitric oxide, 2016)
The influence of dietary nitrate (NO3−) supplementation on indices of maximal sprint and intermittent exercise performance is unclear. To investigate the effects of NO3− supplementation on sprint running performance, and cognitive function and exercise performance during the sport-specific Yo-Yo Intermittent Recovery level 1 test (IR1). In a double-blind, randomized, crossover study, 36 male team-sport players received NO3−-rich (BR; 70 mL·day−1; 6.4 mmol of NO3−), and NO3−-depleted (PL; 70 mL·day−1; 0.04 mmol NO3−) beetroot juice for 5 days. On day 5 of supplementation, subjects completed a series of maximal 20-m sprints followed by the Yo-Yo IR1. Cognitive tasks were completed prior to, during and immediately following the Yo-Yo IR1. BR improved sprint split times relative to PL at 20 m (1.2%; BR 3.98 ± 0.18 vs. PL 4.03 ± 0.19 s; P < 0.05), 10 m (1.6%; BR 2.53 ± 0.12 vs. PL 2.57 ± 0.19 s; P < 0.05) and 5 m (2.3%; BR 1.73 ± 0.09 vs. PL 1.77 ± 0.09 s; P < 0.05). The distance covered in the Yo-Yo IR1 test improved by 3.9% (BR 1422 ± 502 vs. PL 1369 ± 505 m; P < 0.05). The reaction time to the cognitive tasks was shorter in BR (615 ± 98 ms) than PL (645 ± 120 ms; P < 0.05) at rest but not during the Yo-Yo IR1. There was no difference in response accuracy. Dietary NO3− supplementation enhances maximal sprint and high-intensity intermittent running performance in competitive team sport players. Our findings suggest that NO3− supplementation has the potential to improve performance in single-sprint or multiple-sprint (team) sports. •We investigate the effects of dietary nitrate on sprint running speed and high-intensity intermittent running performance.•36 male team-sport players received NO3−-rich (BR; 6.4 mmol NO3−), and NO3−-depleted (PL) beetroot juice for 5 days.•BR improved 20 m sprint performance relative to PL (1.2%; P < 0.05).•BR also improved the distance covered in the Yo-Yo IR1 test relative to PL (3.9%; P < 0.05).•Dietary nitrate enhances maximal sprint and high-intensity intermittent running performance in team sport players.